Jose Rizal. - Rizal, Jose (1861-1896); Abaya, Marilou Diaz
3 CDs, winner of over 70 major and local international film awards.
"What matters death if one dies for what one loves for native land and cherished ones?"
Keywords: Montano, Cesar (Actor).; Motion pictures; Rizal y Alonzo, Jose